Youth Engagement in Policy Making: A Pathway to Inclusive Governance - Faheem Ahmed; Jameel Ahmed; Tahseen Akhtar; Muhammad Kamran (Journal for Social Science Archives, 2025)
Youth engagement is becoming more and more important in modern governance, especially when it comes to inclusive policy making. This study examined how engaging young people in decision making can create more inclusive governance when youth take part they bring new ideas, better understanding of technology, future focused thinking, and these contributions make policies stronger, more practical, and better suited to the need of society. In contemporary governance systems a significant gap exists between policy formulation and representation of younger population, resulting in limited consideration of their needs and perspective, previous research has highlighted the importance of participation in governance, however the specific contribution of youth in shaping responsive and equitable policies reminded underexplored. This study aimed to analyze the relationship between youth participation and inclusive policy outcomes within selected governance settings. This study examined a qualitative research methodology by using document analysis and policy reports, academic literature, and institutional frameworks to identify pattern of youth involvement in decision making processes, the findings revealed that increased youth participation contributed to improved transparency, innovation, and responsiveness in policy development, additionally youth led initiatives were associated with more inclusive approaches in addressing issues related to education, employment, healthcare access, and economic opportunities. The study concludes that youth engagement strengthens the foundation of inclusive governance by promoting participatory decision making and intergenerational equity.